Microbes on the Mobile Phones of Healthcare Workers in Palestine: Identification, Characterization, and Comparison - Mohammad Qadi; Rasha Khayyat; Mohammed A. AlHajhamad; Yazan I. Naji; Beesan Maraqa; Kais Abuzaitoun; Ahmed Mousa; Maysa Daqqa (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Healthcare workers (HCWs) may be using their mobile phones (MPs) to carry microbes that cause hospital-acquired and community infections in general. With antibiotic resistance problem emergence, these infections can be challenging to eradicate. Hence, this study aimed to determine the microbial contamination of HCW MPs and identify and classify bacterial isolates in Palestine. Methods. This was a 7-month comparative cross-sectional analysis of 200 HCW MPs from 2 hospitals and 100 MPs from university students (non-HCWs). Data collection was done using a self-administrated questionnaire, and a swab sample from both HCW and non-HCW MPs was obtained and transferred to An-Najah National University (NNU) microbiology lab for bacterial identification and antibiotic susceptibility. Data were analyzed using Social Sciences Statistical Package (SPSS) version 22.0. Result. Among HCWs, the microbial contamination was 87.5%. Coagulase-negative staphylococci (CoNS; 67.3%), methicillin-sensitive Staphylococcus aureus (MSSA; 17.5%), Gram-positive bacilli (4.1%), methicillin-resistant Staphylococcus aureus (MRSA; 1.6%), and Gram-negative species (1.6%) were the most predominant bacterial isolates. More than half of staphylococci isolates were resistant to penicillin and erythromycin. Male gender, using a mobile phone in the bathroom, and entry to the operating theatre were associated with mobile phone contamination and increased resistance against specific antibiotics. Among non-HCWs, the contamination was 86%. The most predominant bacterial isolates were CoNS, MSSA, and Gram-positive bacilli, with a contamination of 66.8%, 28.5%, and 2.6%, respectively. No MRSA or Gram-negative species were detected in this group. Antibiotic resistance percentage of staphylococci was nearly half of that yielded in the HCW group against each antibiotic. Conclusion. Significant numbers of bacteria have been isolated from HCW MPs. Working in a hospital environment frequently raises the probability of presence of antibiotic-resistant bacteria on a MP. Therefore, infection control teams should discuss methods to prevent the transmission of drug-resistant pathogens from HCW MPs.